Obtention of intergeneric hybrids Helianthus annuus x Tithonia rotundifolia and their morphological and molecular analysis - Luévanos-Escareño, Miriam Paulina; Reyes-Valdés, M. Humberto; Villarreal-Quintanilla, José Ángel; Rodríguez-Herrera, Raúl (Instituto de Ecología, A.C., 2010)
Hybridization between the cultivated sunflower Helianthus annuus and the wild species with ornamental potential Tithonia rotundifolia was performed. From three cultivated materials: AN-3, Primavera and HA 89, the only success was obtained with the public cultivated sunflower line HA 89 as female parent. The male parent was a T. rotundifolia population collected in the state of Guerrero, Mexico. A total of 826 well developed hybrid achenes were produced, with a rate of success of four in 1000 potential achenes. In a sample of 49 plants established in the experimental field, two phenotypic classes were observed: a) plants with many small inflorescenses, and b) plants with a single big head and a few or none axillary inflorescenses. Both types were morphologically characterized and showed a clearly hybrid morphology. Additionally, the AFLP-based DNA fingerprints were analyzed in a sample of ten familial trios, with an average of 28 polymorphisms per trio. The DNA fingerprinting analysis of the plants complemented the morphological study, allowed confirmation of the hybrid nature of the progenies and ruled out the partial hybridization phenomenon. All the hybrid plants showed sterility. From this work, it becomes clear that chromosomic manipulation or tissue culture techniques are needed to develop fertile hybrids with ornamental potential.